2011
DOI: 10.1063/1.3587112
|View full text |Cite
|
Sign up to set email alerts
|

Potential profile near singularity point in kinetic Tonks-Langmuir discharges as a function of the ion sources temperature

Abstract: A plasma-sheath transition analysis requires a reliable mathematical expression for the plasma potential profile UðxÞ near the sheath edge x s in the limit e k D =' ¼ 0 (where k D is the Debye length and ' is a proper characteristic length of the discharge). Such expressions have been explicitly calculated for the fluid model and the singular (cold ion source) kinetic model, where exact analytic solutions for plasma equation (e ¼ 0) are known, but not for the regular (warm ion source) kinetic model, where no a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 21 publications
1
12
0
Order By: Relevance
“…U s (we remind that U 0 and U s 0) and are in accordance with the results of Ref. 10. Quite formally, the relations (41) and (42) can be extended for the region where U U s , assuming…”
Section: The Presheath In the Warm Ion-source Casesupporting
confidence: 57%
See 1 more Smart Citation
“…U s (we remind that U 0 and U s 0) and are in accordance with the results of Ref. 10. Quite formally, the relations (41) and (42) can be extended for the region where U U s , assuming…”
Section: The Presheath In the Warm Ion-source Casesupporting
confidence: 57%
“…To present time, several papers [8][9][10][11][12][13] have been published, where the thermal motion of the neutral gas is taken into account. But, in all these papers, the characteristics of only quasineutral presheath are investigated (In citations above, to our knowledge, the complete number of papers dedicated to the problem is given).…”
Section: Introductionmentioning
confidence: 99%
“…The obtained results are in very good agreement with the model of Jelić [2] made for cold ion source in collision free plasma model. This gives a hope that the code could be used also for the studies of sheath formation in the presence of warm ion sources [19][20][21] and/or magnetic field [22][23][24], where at the moment we are still lacking reliable theoretical models. There are of course still some open questions related to the consistency of our simulations.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that the results of this code are in very good agreement with the analytical solutions [11] of the Tonks-Langmuir model for the ions born at rest. The code could very probably also be used for the study of sheath formation in more fusion relevant conditions with warm ions [19][20][21] and magnetic field [22][23][24] present. As we have shown above, a small potential difference between the electrode and the plasma can be achieved if a certain reflectivity r for the electrons is introduced for the selected -usually left -electrode.…”
Section: Separate Tracking Of Reflected Electronsmentioning
confidence: 99%
“…7 and 8 and many relevant references can be found in Ref. 8. It is, therefore, not surprising that the problem of the ion temperature effects to the plasma-sheath formation is still mainly studied with one dimensional steady-state fluid models.…”
Section: Introductionmentioning
confidence: 99%